(untitled) (Journal of the College of Basic Education, 2022)
This research deals with the discussion of the taboos of entering Paradise, i.e. the reasons that prevent entering it, and touched on the faith and educational effects of these taboos, so the taboos are listed in this topic: according to what was mentioned in the Holy Qur’an and what the honorable Sunnah showed of the first and greatest of the major sins, which is associating partners with God and mentioning the rest of the taboos , And addressing the effects of faith, i.e. the spiritual reflection resulting from these taboos by following them or ending them, and the educational effects and what they represent in terms of reward and punishment on the part of the educator and the recipient in forbidding these taboos.